2017
DOI: 10.1002/anie.201706301
|View full text |Cite
|
Sign up to set email alerts
|

DNA Trojan Horses: Self‐Assembled Floxuridine‐Containing DNA Polyhedra for Cancer Therapy

Abstract: Based on their structural similarity to natural nucleobases, nucleoside analogue therapeutics were integrated into DNA strands through conventional solid‐phase synthesis. By elaborately designing their sequences, floxuridine‐integrated DNA strands were synthesized and self‐assembled into well‐defined DNA polyhedra with definite drug‐loading ratios as well as tunable size and morphology. As a novel drug delivery system, these drug‐containing DNA polyhedra could ideally mimic the Trojan Horse to deliver chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
92
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 37 publications
0
92
0
3
Order By: Relevance
“…The smallest DNA nanorectangles (32 nm × 12 nm) enter more cells than the longer and wider DNA nanorectangles (e.g., 64 nm × 24 nm) as well as the DNA nanotubes, although it is uncertain whether the differences in uptake among these structures are statistically significant. In 2017, Mou et al prepared fluorescently labeled DNA TDNs, dodecahedra, and buckyballs, and assessed their cellular uptake, keeping the total amounts of fluorophore added to the cells constant . By confocal imaging and flow cytometry, the authors observed that the DNA buckyballs (with a reported diameter of 84 nm) enter HeLa cells more abundantly than the other two smaller structures (with an estimated diameter of ≈16 nm for TDN and ≈55 nm for dodecahedron based on our analysis of their published atomic force microscopy (AFM) data).…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…The smallest DNA nanorectangles (32 nm × 12 nm) enter more cells than the longer and wider DNA nanorectangles (e.g., 64 nm × 24 nm) as well as the DNA nanotubes, although it is uncertain whether the differences in uptake among these structures are statistically significant. In 2017, Mou et al prepared fluorescently labeled DNA TDNs, dodecahedra, and buckyballs, and assessed their cellular uptake, keeping the total amounts of fluorophore added to the cells constant . By confocal imaging and flow cytometry, the authors observed that the DNA buckyballs (with a reported diameter of 84 nm) enter HeLa cells more abundantly than the other two smaller structures (with an estimated diameter of ≈16 nm for TDN and ≈55 nm for dodecahedron based on our analysis of their published atomic force microscopy (AFM) data).…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…[9] Thus far, by non-covalently or covalently loading chemotherapeutics onto DNAn anostructures,avariety of DNA-based DDSs have been constructed to deliver chemodrugs either in vitro or in vivo. [12] Despite the advances in precise control over composition and morphology,t his strategy is strictly limited to NAsthat can be converted into phosphoramidte for solidphase synthesis.T oe xpand the drug scope that can be precisely loaded on DNA, it is unmet to develop new strategies for the DDC synthesis.B ased on the fact that phosphorothioate group in PS-modified DNA( PS-DNA) is ag ood nucleophile and more reactive than phosphodiester group,f unctional molecules such as fluorescent dyes, [13] proteins, [14] gold nanoparticles, [15] have been conjugated onto DNAs trands at PS sites.P articularly,a fter modifying the chemodrug with electrophile moiety,weonce showed that PS-DNAc ould be efficiently grafted with am ultitude of paclitaxels and subsequently self-assemble into am icellular nanodrug. [11] Recently,w ep roposed as trategy that integrated nucleoside analogues (NAs) into DNAstrands and then assembled them into well-defined DNAn anostructures to construct precise nanomedicine.…”
mentioning
confidence: 99%
“…[2] Among these drug modules, therapeutic nucleoside and nucleobase analogues show inherent advantages for their excellent stability during DNA synthesis. [3] …”
mentioning
confidence: 99%
“…[4] Recently, floxuridine was employed to construct fluoropyrimidine polymer (F10) and to pair with guanosine in a DNA polyhedral nanosystem for cancer therapy. [3c, 5] But, in spite of these advances, drug-incorporated oligonucleotides, consistent with natural oligonucleotides, face challenges in systemic delivery. [6] Conventional methods focus on chemical modifications with active targeting ligands and conjugation with nanoparticles which accumulate in the tumor by the EPR effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation